Development and use of an animal model to study post‐traumatic stiffness and contracture of the elbow. Issue 2 (31st July 2015) - Lake, Spencer P.; Castile, Ryan M.; Borinsky, Stephanie; Dunham, Chelsey L.; Havlioglu, Necat; Galatz, Leesa M.
ABSTRACT: Post‐traumatic joint stiffness (PTJS) of the elbow is a debilitating condition that poses unique treatment challenges. While previous research has implicated capsular tissue in PTJS, much regarding the development and progression of this condition remains unknown. The objective of this study was to develop an animal model of post‐traumatic elbow contracture and evaluate its potential for studying the etiology of PTJS. The Long‐Evans rat was identified as the most appropriate species/ breed for development due to anatomical and functional similarities to the human elbow joint. Two surgical protocols of varying severity were utilized to replicate soft tissue damage seen in elbow subluxation/dislocation injuries, including anterior capsulotomy and lateral collateral ligament transection, followed by 6 weeks of unilateral joint immobilization. Following sacrifice, flexion‐extension mechanical joint testing demonstrated decreased range‐of‐motion and increased stiffness for injured‐immobilized limbs compared to control and sham animals, where functional impact correlated with severity of injury. Histological evaluation showed increased cellularity, adhesion, and thickness of capsule tissue in injured limbs, consistent with clinical evidence. To our knowledge, this is the first animal model capable of examining challenges unique to the anatomically and biomechanically complex elbow joint. Future studies will use this animal model to investigate mechanisms responsible for PTJS. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:354–364, 2016.